Frequency of Physical Problem among 7-11 Years Old Children in Foster Care Centers - Mahboubeh Bayat; Mahboubeh Nazari-Jeyrani; Arezou Shahsavari; Majid Miri; Mahin Naderifar (Iran University of Medical Sciences, 2010)
Background and Aim: Every year, thousands of children are admitted in foster care centers, mostly because of neglect, physical abuse, parental substance abuse, and divorce and socio- economic poverty. On the other hand, entring these centers and living there faces children with a lot of behavioral and health problems. The purpose of this study was to assess physical health status among 7-11 years old children living in foster care centers in Tehran.   Material and Method: We performed a cross-sectional study with 105 children (57 boys, 48 girls). Census sampling was used to recruit participants and information about child physical health was obtained by physical exams based on child health assessment form, child health records and sometimes, consults with physicians.   Results: Findings showed that most frequently type of physical problem in these children was periodontal (90.5%), followed by skin (76.2%), eyes (51.4%), and respiratory system problems (40.1%). Chi-square test did not show any statistical significant relationship of physical health with sex, age and duration of stay in these centers.   Conclusion: Based on the finding, full attention and health facility should be given to this group of children and more studies are needed to study the factors affecting their health.